THE EVOLUTION OF INDIAN ENGLISH DRAMA: FROM RABINDRANATH TAGORE TO MAHESH DATTANI - V, Chandrasekhar Naik; Biradar, Dr. Renuka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research paper explores the evolution, significance, and contemporary relevance of Indian English Drama, with a focus on key playwrights Rabindranath Tagore and Mahesh Dattani. Beginning with an examination of the socio-political backdrop of post-independence India, it traces the transition of Indian English Drama from its early influences to the present era. The contrasting themes and styles between Tagore and Dattani are analysed, highlighting the shift from poetic lyricism to gritty realism, and the exploration of universal truths to pressing social issues.The paper underscores the reflection of modern India in Indian English Drama, portraying the diverse complexities and contradictions of society. It discusses the pivotal role of Indian English Drama in shaping cultural discourse, fostering critical dialogue, and advocating for social change. Despite facing challenges such as economic constraints and digital competition, Indian English Drama presents numerous opportunities for growth and innovation, particularly in the digital age.The paper concludes with a call to appreciate the importance of understanding the evolution of Indian English Drama and its future prospects. By embracing diversity, inclusivity, and innovation, Indian English Drama can continue to thrive and inspire audiences’ worldwide, sparking important conversations about the human experience and the pressing issues of our time.